The Existence and Legal Problems of Pak Ogah in Indonesia - Adhi Putra Satria (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
Pak Ogah is a citizen, either an individual or a group that participates in regulating traffic order in the hope of being rewarded by road users who will pass or turn around at intersections in major cities in Indonesia. In this study, the issues will be presented that factors influence the emergence of Pak Ogah, and what legal problems arise from the phenomenon. The method used in this study is a qualitative research method with a juridical-empirical approach which uses facts in the field as the primary data. The results of the study stated that the emergence of the phenomenon of Pak Ogah was caused by three main factors, namely the legal substance, legal structure (law enforcement officers), and the legal culture of the Indonesian people. Furthermore, the problem arising from the phenomenon is that there is no legal guarantee and work safety for the protection of Pak Ogah if an accident occurs when regulating traffic order.